The water efficient Landscape - Rayno, Valerie (2016)
Water efficiency in the landscape is becoming an increasingly pressing issue in the United States, as water shortages become more and more common. While awareness of water issues have increased over the last decades, landscape irrigation still constitutes a large percentage of household water consumption in the United States, and therefore reducing water use in the landscape is a vital step for conservation. North Carolina receives between 40” – 55” (1000mm-‐1400mm) of rain a year and has always been considered a water-‐rich state, however even with its abundant yearly rainfall, recent years have lead to water shortages. Water-‐efficient gardening is the practice of landscaping with water conservation in mind. It includes xeriscaping and the idea of grouping plant material based on their water requirements, using plants that are well suited to the site conditions and require no supplemental irrigation, and increasing a soil’s absorption rate and water retention. This paper explores the principles of xeriscaping and suggests suitable water-‐wise plants for residential landscapes in the piedmont region of North Carolina.